PENGARUH ECONOMIC VALUE ADDED, RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PT. MNC KAPITAL INDONESIA,Tbk - Yolanda Yolanda; Fariza Putri Fami (Jurnal Manajemen FE-UB, 2020)
This study aims to obtain empirical evidence of the influence of factors related to thecompany value of PT. MNC Kapital Indonesia Tbk. These factors include the Economic ValueAdded, Return On Asset and Debt To Equity Ratio which later functioned as independentvariables which influenced the company value which functioned as the dependent variable. Theresearch method used in this study is multiple linear regression.The results showed that simultaneously economic value added, return on assets, debt toequity ratio, have a significant effect on firm value. economic value added, return on assets, anddebt to equity ratio partially have a significant and positive effect on company value.Keywords:company value, economic value added, return on assets, debt to equity ratio